dk \(\hept{\begin{cases}x\left(3x+1\right)\ge0\\x\left(x-1\right)\ge0\end{cases}< =>\orbr{\begin{cases}x\ge1\\x\le\frac{-1}{3}\end{cases}}}\)
vì x khác 0 nên chia cả 2 vế cho \(\sqrt{x}\)ta được \(\sqrt{3x+1}-\sqrt{x-1}=2\sqrt{x}< =>\)\(\sqrt{x-1}+2\sqrt{x}-\sqrt{3x+1}=0< =>\)\(\sqrt{x-1}+\frac{4x-\left(3x+1\right)}{2\sqrt{x}+\sqrt{3x+1}}=0\)\(\sqrt{x-1}+\frac{x-1}{2\sqrt{x}+\sqrt{3x+1}}=0\)\(< =>\sqrt{x-1}\left(1+\frac{\sqrt{x-1}}{2\sqrt{x}+\sqrt{3x+1}}\right)=0< =>\sqrt{x-1}=0\) (vì biểu thức trong ngoặc luôn \(\ge1\)) <=> x-1= 0 <=> x=1 (thỏa mãn điều kiện)
Đúng 0
Bình luận (0)